Green formation of spherical and dendritic silver nanostructures under microwave irradiation without reducing agent - Noroozi, Monir; Zakaria, Azmi; Abd. Moksin, Mohd Maarof; Abdul Wahab, Zaidan; Abedini, Alam (MDPI, 2012)
The rapid and green formation of spherical and dendritic silver nanostructures based on microwave irradiation time was investigated. Silver nanoparticles were successfully fabricated by reduction of Ag+ in a water medium and using polyvinylpyrrolidone (PVP) as the stabilizing agent and without the use of any other reducing agent, and were compared with those synthesized by conventional heating method. UV–vis absorption spectrometry, transmission electron microscopy (TEM), atomic absorption spectroscopy (AAS) and photon correlation spectroscopy (PCS) measurements, indicated that increasing the irradiation time enhanced the concentration of silver nanoparticles and slightly increased the particle size. There was a lack of large silver nanoparticles at a high concentration, but interestingly, the formation and growth of silver dendrite nanostructures appeared. Compared to conventional heating methods, the silver nanoparticle suspension produced by irradiated microwaves was more stable over a six-month period in aqueous solution without any signs of precipitation.